On Abbotsford - Archer-Thompson, Kirsty (Romanticism on the Net)

(untitled) (Université de Montréal, 2023)
The process of curating a writer or artist’s home and collections rewards the curator with a series of vignettes of their daily life and creative process. However, in this video, Archer-Thompson, the Curator of Abbotsford, explores the significance of a view itself, notably the last view that Sir Walter Scott surveyed from his deathbed through the dining-room window of his beloved home. For the many visitors who came in search of Scott after his death with their guidebooks and Waverley Novels in hand, this window would mark a place in the house peculiarly charged with emotion and Romantic resonance.